2004
DOI: 10.1038/sj.emboj.7600043
|View full text |Cite
|
Sign up to set email alerts
|

Nhp6 facilitates Aft1 binding and Ssn6 recruitment, both essential for FRE2 transcriptional activation

Abstract: We found Nhp6a/b yeast HMG-box chromatin-associated architectural factors and Ssn6 (Cyc8) corepressor to be crucial transcriptional coactivators of FRE2 gene. FRE2 encoding a plasma membrane ferric reductase is induced by the iron-responsive, DNA-binding, transcriptional activator Aft1. We have shown that Nhp6 interacts directly with the Aft1 N-half, including the DNA-binding region, to facilitate Aft1 binding at FRE2 UAS. Ssn6 also interacts directly with the Aft1 N-half and is recruited on FRE2 promoter only… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
46
1
2

Year Published

2004
2004
2011
2011

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(50 citation statements)
references
References 46 publications
1
46
1
2
Order By: Relevance
“…We disfavor the formal possibility that Cyc8-Tup1, by virtue of being a large complex, occludes interactions between coactivators and DNA, thereby reducing the stable association of these coactivators at Tup1 target genes. Aside from being ad hoc, this formal possibility is inconsistent with previous observations that Tup1 can co-occupy target sites with Swi/Snf and SAGA (Proft and Struhl 2002) and that it can increase recruitment of these coactivators to target sites upon stress (Papamichos-Chronakis et al 2002;Proft and Struhl 2002;Fragiadakis et al 2004;Kim et al 2005;Desimone and Laney 2010). In addition, repression models that invoke specific chromatin changes directly mediated by Cyc8-Tup1 do not explain the near-immediate kinetic link between the reciprocal occupancies by Cyc8-Tup1 and three distinct coactivator complexes.…”
Section: Tup1 Repression Occurs Primarily By Masking Activation Domaicontrasting
confidence: 53%
See 1 more Smart Citation
“…We disfavor the formal possibility that Cyc8-Tup1, by virtue of being a large complex, occludes interactions between coactivators and DNA, thereby reducing the stable association of these coactivators at Tup1 target genes. Aside from being ad hoc, this formal possibility is inconsistent with previous observations that Tup1 can co-occupy target sites with Swi/Snf and SAGA (Proft and Struhl 2002) and that it can increase recruitment of these coactivators to target sites upon stress (Papamichos-Chronakis et al 2002;Proft and Struhl 2002;Fragiadakis et al 2004;Kim et al 2005;Desimone and Laney 2010). In addition, repression models that invoke specific chromatin changes directly mediated by Cyc8-Tup1 do not explain the near-immediate kinetic link between the reciprocal occupancies by Cyc8-Tup1 and three distinct coactivator complexes.…”
Section: Tup1 Repression Occurs Primarily By Masking Activation Domaicontrasting
confidence: 53%
“…Interestingly, in response to osmotic or carbon source stress, Cyc8-Tup1 does not dissociate from target promoters, and in fact it contributes to recruitment of the Swi/Snf and SAGA coactivator complexes (Papamichos-Chronakis et al 2002;Proft and Struhl 2002;Mennella et al 2003). In these and other cases (Fragiadakis et al 2004;Zhang and Reese 2005;Hickman and Winston 2007), the DNA-binding repressor also appears to function as an activator protein under appropriate stress conditions.…”
mentioning
confidence: 99%
“…In addition, cell type-specific and DNA damage-inducible promoters are only occupied by the Ssn6-Tup1 complex under repressive conditions (51,52) ruling out any involvement of Ssn6-Tup1 in activation of this set of genes. More recently, it has been shown that the recruitment of the Ssn6-Tup1 complex to iron-regulated promoters such as FRE2 and ARN2 is essential for gene activation (26). In addition, studies in S. cerevisiae and Candida albicans have shown that cells defective in Tup1 de-repress the iron-siderophore uptake system (53,54).…”
Section: Discussionmentioning
confidence: 99%
“…This is possible because the Cti6 protein interacts simultaneously with the Ssn6-Tup1 and SAGA complexes, and mediates SAGA and TBP recruitment, histone acetylation, and transcriptional activation (17). Interestingly, recent studies in S. cerevisiae and Schizosaccharomyces pombe have also shown that the Tup1 complex (Tup11/Tup12 in S. pombe) modulates the expression of iron-regulated genes by associating with the Aft1 (Fep1 in S. pombe) transcription factor (25,26). …”
mentioning
confidence: 99%
“…Nhp6 is encoded by two genes, NHP6A and NHP6B. No phenotype is seen in nhp6a and nhp6b single mutants, while the nhp6a nhp6b double mutant (which we will describe as nhp6ab) is temperature sensitive for growth (Costigan et al 1994) and shows transcriptional defects (Paull et al 1996;Yu et al 2000;Fragiadakis et al 2004). Nhp6 also functions with Spt16 and Pob3, as part of the yeast FACT complex, to promote transcriptional elongation (Formosa et al 2001), and Nhp6 is important for expression of the SNR6 gene, transcribed by RNA polymerase III (Kruppa et al 2001;Lopez et al 2001;Martin et al 2001).…”
mentioning
confidence: 99%